The preparation of BODIPY and porphyrin dyes and their cyclodextrin inclusion complexes and PluronicÂ® F-127 encapsulation micelles for use in PDT and PACT - Molupe, Nthabeleng (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
Several novel BODIPY dyes ((4,4"²-difluoro-1,7-tetramethyl-3,5-(3-dithiophene)-2,6-diiodo-8-(4-dimethylamino)-4-bora-3a,4a-diaza-s-indacene (1c), 4,4"²-difluoro-1,7-tetramethyl-3,5-(3 dithiophene)-2,6-diiodo-8-(4-methylthio)-4-bora-3a,4a-diaza-s-indacene (3c) and 4,4"²-difluoro-1,7-tetramethyl-3,5-(4-dibenzyloxybenzene)-2,6-diiodo-8-(4-methylbenzoate)-4 bora-3a,4a-diaza-s-indacene (4c)) and porphyrins (tetraacenaphthylporphyrin (7a) and Sn(IV) tetraacenaphthylporphyrin (7b)) were synthesized and characterized. Previously reported BODIPY dyes (4,4"²-difluoro-1,7-tetramethyl-3,5-(2-dihydroxy)-2,6-diiodo-8-(4-bromo)-4-bora-3a,4a-diaza-s-indacene (5) and 4,4"²-difluoro-1,7-tetramethyl-3,5-(2-dithiophene)-2,6-diiodo-8-(phenyl)-4-bora-3a,4a-diaza-s-indacene (6)) were also used. PluronicÂ® F-127 and cyclodextrins were used as solubilizing drug delivery agents for the synthesized BODIPY dyes. The encapsulation of BODIPY dyes with PluronicÂ® F-127 micelles improved the water solubility of the BODIPY 5. Further modification of PluronicÂ® F-127 by coating with folate-functionalized chitosan for targeted delivery of BODIPY 1c and 6 was explored. The BODIPY dyes and their encapsulation complexes exhibited significant inhibition of human MCF-7 breast cancer cell growth. When cyclodextrins were used as nanocarriers, the inclusion complexes of BODIPY 4c with mÎ²CD were found to enhance the water-solubility of the dye. Greater photoinactivation of Staphylococcus aureus was observed for the inclusion complexes when compared to the effect of solutions of non-complexed BODIPY 4c. The cyclodextrin inclusion complexes of porphyrin 7b with mÎ²CD were also found to enhance the water-solubility of 7b. When the photodynamic effect was evaluated, solutions of the porphyrin alone and their inclusion complexes were found to have significant photodynamic effects against human MCF-7 breast cancer cells.
Keywords: Dyes and dyeing -- Chemistry; Drug delivery systems; Fluorescence spectroscopy; Cancer -- Photochemotherapy; Photosensitizing compounds -- Therapeutic use; Cyclodextrins -- Biotechnology; Nanoparticles